Bridging the Gap in Mathematics Education: The Efficacy of Deep Learning and STEM-Based PBL on Critical Thinking - Farikha Aulia Rahma; Megita Dwi Pamungkas; Fadhilah Rahmawati (Jurnal Pendidikan MIPA, 2026)
Critical thinking skills are important for students to face challenges in the 21st century, but their development in mathematics learning still has limitations because the approach tends to use conventional methods whose center is the teacher. This study aims to analyze the effectiveness of deep learning methods in improving students' critical thinking skills in mathematics. The deep learning method, implemented with the principles of meaningful, mindful, and joyful learning, used a STEM-based Problem-Based Learning model. This method focused on analyzing real-world problems, working in groups, group discussions, and applying trigonometry concepts to real-world problems through project-based activities. The study used a quasi-experimental pretest–posttest control group design involving 71 students in class X at SMA Negeri 2 Magelang for the 2025/2026 school year. The experimental group received instruction using the deep learning method through the Problem-Based Learning model, based on STEM and trigonometry material, while the control group used conventional instruction. The instrument used in this study is a validated critical-thinking test with five factors: interpretation, analysis, evaluation, inference, and explanation. The results of the paired-sample t-test indicated a significant improvement in both groups (p < 0.001). The experimental group achieved a mean gain score of 38.43, while the control group recorded a mean gain of 30.97 points from the pretest to posttest.  The independent-samples t-test also indicated a significant difference in posttest scores between the two groups (p = 0.024). These results indicate that the deep learning method is more effective than traditional learning in improving critical thinking in mathematics learning. Keywords: critical thinking, deep learning approach, mathematics education.